Environmental behavior and associated plant accumulation of silver nanoparticles in the presence of dissolved humic and fulvic acid. (December 2018) - Li, Yong; Chen, Haiyan; Wang, Fei; Zhao, Furong; Han, Xiaomin; Geng, Huanhuan; Gao, Ling; Chen, Huilun; Yuan, Rongfang; Yao, Jun
Abstract: This work investigated the role of natural organic matter (NOM) in the environmental processes of silver nanoparticles (AgNP) and the uptake and accumulation of AgNP in wheat. Different NOMs (Suwannee River humic acids [SRHA], fulvic acid [FA]) and Ag elements (Ag (0) and Ag + ) were incubated in a hydroponic media for 15 days. The results showed that the NOM (10 mg C L −1 ) altered the dissolution, stabilization, uptake and accumulation of AgNP. The dissolution of AgNP declined in the presence of NOM. Compared with FA, the dissolved Ag + decreased much more from 0.30 mg L −1 to 0.10 mg L −1 in the presence of SRHA. The fluorescence quenching results indicated that SRHA exhibited stronger binding to Ag + than that of FA, and the quenching constants K sv were 0.1309 (SRHA) and 0.0074 (FA), respectively. CO, CH, COC, and MeOH were involved in the interaction between NOM and AgNP. The NOM decreased the accumulated content of Ag in wheat. Hence, NOM alleviated the inhibition of AgNP to wheat growth. SRHA reduced the Ag content of wheat roots approximately 3-fold. These results clearly indicated the importance of NOM on altering the behavior, fate and toxicity of AgNP in an environment. Graphical abstract: Image 1 Highlights: Dissolved humic and fulvic acid reduced the dissolution and promoted the dispersion of AgNP in pH 5–8. The fluorophore strength of NOM was proportional to the concentration of added silver ions, and Ksv: SRHA > FA. CO, CH, COC and MeOH functional groups contributed to the interaction between NOM and AgNP. Dissolved humic and fulvic acid alleviated the growth inhibition of wheat by AgNP. Dissolved humic and fulvic acid decreased the accumulation content of Ag in wheat. Abstract : NOM reduced the dissolution of Ag NP to further alleviate inhibition for wheat growth.